Adansonia digitata leaf extract mediated synthesis of silver nanoparticles; characterization and antimicrobial studies - Chennareddy Maruti Kesava Kumar,Pulicherla Yugandhar,Nataru Savithramma (Journal of Applied Pharmaceutical Science, 2015)
Objectives: In the present study we report a simple, eco-friendly and cost effective method for synthesis of silver nanoparticles (SNPs) from Adansonia digitata leaf extract and perform to know the antimicrobial potency on 07 bacterial and 05 fungal pathogens. Materials and Method: These green synthesized nanoparticles are characterized by UV-VIS spectroscopy, FTIR, XRD, AFM, SEM, TEM and to know the antimicrobial potency of nanoparticles by disc diffusion method. Results and Discussion: A broad peak obtained at 431 nm of UV-VIS spectroscopic analysis confirms the synthesized nanoparticles are silver. Phenols and proteins of leaf extract is main responsible for reduction and stabilization of these nanoparticles confirmed by FTIR. XRD pattern of synthesized nanoparticles confirms the particles are crystalline in nature and owing 44 nm in size. EDAX analysis shows 34.22 weight percentage of Ag material in the reaction medium indicates purity of sample. High resolution microscopic studies with AFM, SEM and TEM analysis reveals the nanoparticles are polydispersed in condition, spherical in shape, having the size range from 5 to 64 nm without any agglomeration. Further, the antimicrobial studies confirm the nanoparticles having broad range of antimicrobial efficacy against clinically isolated pathogenic microorganisms.Conclusions: SNPs synthesized by using Adansonia digitata leaf extract acts as effective reducing agent for production of narrow range size of SNPs. This method provides pave a way for green, cost effective and eco-friendly method for production of SNPs and can be used as effective antimicrobial agents on clinically isolated microbial pathogens.
Keywords: Adansonia digitata,Silver nanoparticles,Characterization,Antimicrobial activity.